Technology foresight for implementing mobile number portability (MNP) in the Philippines using scenario building - Mariano, Cecile Manuel (University of the Philippines Diliman, 2014)
The world today is experiencing innovation and technology at its finest. With the advancement of technology and innovation, there are endless possibilities emerging into reality to which we all benefit from . May it be in any industry, undeniably, technology has helped shape and develop our civilization and our way of living today. It has made countless lives easier and has helped us utilize time more efficiently to create a better society with endless possibilities. In light of this technological boom, mobile phones have become a part of almost every person, in the case of this study, the Filipino, both young and old, because of the multiple purposes it serves. Mobile phone users therefore are slowly moving towards a single number. It is for this reason that in most countries, such as the Philippines, Filipinos have made their mobile telephone number their personal alternative identifier, consequently almost completely eradicating the option of changing numbers. For mobile users, their mobile numbers have become their ownership and therefore have become personal to them since most of them have had their mobile numbers for the longest time. Aside from that, consumers nowadays have become more mobile and therefore would rather prefer to be reached anytime and anywhere with their mobile devices. And with a single number in place, personal mobility becomes possible. Telecommunications (Telco) Industry in the Philippines has become one of the most competitive industries in the country today. More particularly, the mobile sector has become the game changer in human behavior as well as a significant player in the economy. It is therefore essential to maximize and utilize this mobile craze to the country's advantage for economic growth and respond appropriately to technological advancement and innovation. However, the Philippines' Telco Industry is a duopoly type composing of the two giants- Smart Telecommunications with its subsidiary company, Sun Cellular, and Globe Telecom, causing competition to be stagnant and quality of service to be very poor. And although mobile phone users would want to change network providers due to reasons like poor quality of service and lack of diverse product offerings in the market, they cannot do so since it would compel them to give up their existing numbers. Given the current situation, this study aims to address these issues through Technology Foresight on the plausible implementation of mobile number portability in the Philippines using Scenario Building. Number porting is a service that enables telephone customers to retain their existing telephone numbers even when they switch from one Operator to another.